The Effect of Eco-sustainability Disclosure in Financial Reports on the Market Value of Companies: Company Characteristics as Intermediary Role - Salah Jiyad Kadhim; Nejoom Arar Taher; Hussein Falah Hassan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Environmental issues have become an increasingly significant topic in the accountingliterature in recent decades. The public's apprehension regarding the financial andnon-financial performance of companies has been heightened by environmentalissues associated with industrial activities, which has resulted in a heightened demandfor the disclosure and examination of environmental reports, particularly indeveloped countries. Nevertheless, there is a dearth of research in this field indeveloping countries, particularly in the Arab region, including Iraq. Therefore, thispaper aims at investigating the potential impact of disclosure of eco-sustainability infinancial reports on market value and the effect of disclosure of eco-sustainability infinancial reports on market value under the context of company characteristics (size,age, and loss). This paper draws on the data disclosed by companies listed on the IraqStock Exchange. The hypotheses regarding the impact of eco-sustainabilitydisclosure in financial reports on market value regarding company characteristicswere verified by selecting 35 joint stock companies from 2011 to 2022. This paperreached several conclusions. The effect of disclosures regarding eco-sustainability infinancial reports on market value has been revealed. Additionally, the market value of a company is influenced by the disclosure of eco-sustainability in financial reports, asindicated by the quality descriptors of the company, namely age and losses. Thepaper also found out that the disclosure of eco-sustainability in financial reports doesnot affect the market value of the company under the company qualities, as measuredby the company's size.